2009
DOI: 10.1371/journal.pone.0007615
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine-Rich Peptides Potently Bind ESAT6, a Virulence Determinant of Mycobacterium tuberculosis, and Concurrently Affect the Pathogen's Growth

Abstract: BackgroundThe secretory proteins of Mycobacterium tuberculosis (M. tuberculosis) have been known to be involved in the virulence, pathogenesis as well as proliferation of the pathogen. Among this set, many proteins have been hypothesized to play a critical role at the genesis of the onset of infection, the primary site of which is invariably the human lung.Methodology/Principal FindingsDuring our efforts to isolate potential binding partners of key secretory proteins of M. tuberculosis from a human lung protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 42 publications
(50 reference statements)
2
29
0
Order By: Relevance
“…The molecular interaction between RpoE and ChrR was studied by using the BacterioMatch II two-hybrid system using E. coli as a host (Kumar et al, 2009). The transformants carrying the two recombinant plasmids, one expressing RpoE and the other expressing ChrR, displayed a LacZ + phenotype and produced blue colonies on X-Gal plates, indicating an interaction between the two proteins.…”
Section: Cotranscription Of Rpoe and Chrr Genes And Interaction Of Rmentioning
confidence: 99%
“…The molecular interaction between RpoE and ChrR was studied by using the BacterioMatch II two-hybrid system using E. coli as a host (Kumar et al, 2009). The transformants carrying the two recombinant plasmids, one expressing RpoE and the other expressing ChrR, displayed a LacZ + phenotype and produced blue colonies on X-Gal plates, indicating an interaction between the two proteins.…”
Section: Cotranscription Of Rpoe and Chrr Genes And Interaction Of Rmentioning
confidence: 99%
“…Recently, Kumar et al have reported another peptide HCL1, isolated from human lung cDNA library, that shows strong interaction with ESAT6 of both M. tuberculosis as well as M. smegmatis, with its in vivo expression severely impairing M. tuberculosis growth [31]. We decided to test the efficacy of the three-hybrid system using proteins CFP10, ESAT6 and HCL1.…”
Section: Resultsmentioning
confidence: 99%
“…Early ring-stage parasites were incubated with M5 protein (15 mM) and allowed to grow through different developmental stages. For microscopic analysis, smears were made from each well at different time points (10,20,24,30,36, 48 and 52 hpi), fixed and subsequently stained with Giemsa, and the number of parasites at different developmental stages counted.…”
Section: Methodsmentioning
confidence: 99%
“…In control experiments, a similar number of THP-1 macrophages were treated with buffer solution without any protein/polypeptide as well as with a nonspecific protein ARPC4. The treated cells were infected with Mtb H37Rv-GFP (green fluorescent protein) 36 and infection was monitored by detecting GFP fluorescence through flow cytometry. The treated cells were also analysed for the expression of ICAM-1 by using Alexa Fluor 647-conjugated anti-ICAM-1 antibody.…”
Section: Icam-1 Is Involved In Mtb Host-pathogen Interactionsmentioning
confidence: 99%